1995
DOI: 10.1111/j.1365-2958.1995.tb02280.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase‐dependent HPr/CcpA interaction links glycolytic activity to carbon catabolite repression in Gram‐positive bacteria

Abstract: CcpA, the repressor/activator mediating carbon catabolite repression and glucose activation in many Gram-positive bacteria, has been purified from Bacillus megaterium after fusing it to a His tag. CcpA-his immobilized on a Ni-NTA resin specifically interacted with HPr phosphorylated at seryl residue 46. HPr, a phospho-carrier protein of the phosphoenolpyruvate: glycose phosphotransferase system (PTS), can be phosphorylated at two different sites: (i) at His-15 in a PEP-dependent reaction catalysed by enzyme I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
266
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 336 publications
(272 citation statements)
references
References 24 publications
6
266
0
Order By: Relevance
“…A specific interaction between CcpA and P-Ser-HPr was indeed demonstrated by retarded elution of P-SerHPr from CcpA-carrying columns 78) and later by nuclear resonance measurements. 79) In 1995, a complex of CcpA with P-Ser-HPr was verified to recognize the cre of the gnt operon with high affinity in footprinting experiments.…”
Section: Continuedmentioning
confidence: 80%
“…A specific interaction between CcpA and P-Ser-HPr was indeed demonstrated by retarded elution of P-SerHPr from CcpA-carrying columns 78) and later by nuclear resonance measurements. 79) In 1995, a complex of CcpA with P-Ser-HPr was verified to recognize the cre of the gnt operon with high affinity in footprinting experiments.…”
Section: Continuedmentioning
confidence: 80%
“…Phosphorylation of Ser 46 prevents the interaction of HPr with enzyme I, sugar-specific IIA proteins, and possibly with other protein domains (Reizer et al, 1984Deutscher et al, 1995;Ye & Saier, 1995). Although the enzyme I-binding site on B. subtilis HPr has not yet been determined, it has recently been shown to be indistinguishable from the enzyme IIAg"-binding site on HPr in the analogous E. coli proteins (van Nuland et al, 1995).…”
Section: Implications For Hpr Functionmentioning
confidence: 99%
“…HPr(Ser-P) interacts with a remarkably wide variety of proteins to control their activities, whereas neither the unphosphorylated form of HPr nor HPr(His-P) bind to these target proteins (Deutscher et al, 1995;Ye & Saier, 1995). The precise molecular basis for this selective binding is unknown, but it undoubtedly reflects electrostatic and/or conformational changes that accompany phosphorylation of HPr at Ser 46.…”
mentioning
confidence: 99%
“…The trans-acting protein CcpA, a member of the LacI-GalR family of repressors (14), mediates CCR by binding to the cis-active operator sequence cre (catabolite responsive element) (15). An interaction of P-Ser-HPr with CcpA has been demonstrated in vitro, and this interaction is strengthened by FBP (16). Fujita et al (17) have shown that the protein complex formed between CcpA and P-Ser-HPr interacts specifically with the gnt cre.…”
mentioning
confidence: 99%